The origins of Primitive Methodism - Calder, Sandy (Studies in modern British religious history, 2016)
This book shows that while the Primitive Methodist Connexion's mature social character was working-class, this did not reflect its social origins. It was never the church of the working class, the great majority of whose churchgoers went elsewhere: rather it was the church whose commitment to its emotional witness was increasingly incompatible with middle-class pretensions. Sandy Calder shows thatthe Primitive Methodist Connexion was a religious movement led by a fairly prosperous elite of middle-class preachers and lay officials appealing to a respectable working-class constituency. This reality has been obscured by the movement's self-image as a persecuted community of humble Christians, an image crafted by Hugh Bourne, and accepted by later historians, whether Methodists with a denominational agenda to promote or scholars in search of working-class radicals. Primitive Methodists exaggerated their hardships and deliberately under-played their social status and financial success. Primitive Methodism in the later nineteenth and early twentieth centuries became the victim of its own founding mythology, because the legend of a community of persecuted outcasts, concealing its actualrespectability, deterred potential recruits. SANDY CALDER graduated with a PhD in Religious Studies from the Open University and has previously worked in the private sector.